Mucoadhesive Chitosan Delivery System with Chelidonii Herba Lyophilized Extract as a Promising Strategy for Vaginitis Treatment - Paczkowska, Magdalena (J Clin Med, 2020)
Chelidonium majus (also known as celandine) contains pharmacologically active compounds such as isoquinoline alkaloids (e.g., chelidonine, sanguinarine), flavonoids, saponins, carotenoids, and organic acids. Due to the presence of isoquinoline alkaloids, Chelidonii herba extracts are widely used as an antibacterial, antifungal, antiviral (including HSV-1 and HIV-1), and anti-inflammatory agent in the treatment of various diseases, while chitosan is a biocompatible and biodegradable carrier with valuable properties for mucoadhesive formulations preparation. Our work aimed to prepare mucoadhesive vaginal drug delivery systems composed of Chelidonii herba lyophilized extract and chitosan as an effective way to treat vaginitis. The pharmacological safety of usage of isoquinoline alkaloids, based on MTT test, were evaluated for the maximum doses 36.34 ± 0.29 µg/mL and 0.89 ± 1.16 µg/mL for chelidonine and sanguinarine, respectively. Dissolution rate profiles and permeability through artificial membranes for chelidonine and sanguinarine after their introduction into the chitosan system were studied. The low permeability for used save doses of isoquinoline alkaloids and results of microbiological studies allow confirmation that system Chelidonii herba lyophilized extract chitosan 80/500 1:1 (w/w) is a promising strategy for vaginal use. Ex vivo studies of mucoadhesive properties and evaluation of tableting features demonstrated that the formulation containing Chelidonii herba lyophilized extract (120.0 mg) with chitosan (80/500—100.0 mg) and polymer content (HPMC—100.0 mg, microcrystalline cellulose—50.0 mg, lactose monohydrate—30.0 mg and magnesium stearate—4.0 mg) is a vaginal dosage form with prolonging dissolution profile and high mucoadhesion properties (up to 4 h).